IMPROVING THE PERFORMANCE OF DUST COLLECTORS VZP-1200 AND ADDING NEW INNOVATIVE TECHNOLOGIES (Journal of Science-Innovative Research in Uzbekistan, 2023)
The efficiency of the dust collectors has been increased by increasing the efficiency of the dust collectors and trapping the fibrous waste in the air flow and passing the remaining air flow to the dust collector. The calculation of the chain drive installed in the improved equipment and the determination of the number of stars were carried out